Congenital absence of the right coronary artery: A case report and literature review. Issue 12 (March 2018) - Yan, Gao-Wu; Bhetuwal, Anup; Yang, Guo-Qing; Fu, Quan-Shui; Hu, Na; Zhao, Lin-Wei; Chen, Hong; Fan, Xiao-Ping; Yan, Jing; Zeng, Hao; Zhou, Qing
Abstract: Rationale: Congenital absence of the right coronary artery (RCA) is a rare congenital malformation of the cardiovascular system which may have fatal consequences. Patient concerns: A 63-year-old man with a 5-year history of chest pain after exertion which had aggravated for >1 month was advised for admission and computed tomography angiography (CTA) examination of the coronary artery to screen for coronary artery disease (CAD). Diagnoses: The coronary artery CTA showed absence of RCA arising form the aortic root after which a selective coronary angiography (SCA) examination was done that confirmed the diagnosis of congenital absence of RCA. Interventions: As the patient refused to receive a coronary artery stent implantation citing his financial condition, only symptomatic treatment was given. Outcomes: The patient requested to be discharged from the hospital against the advice of his doctors 1 week later. A query made by the telephone suggested that the patient's symptoms were under control by use of prescribed medications only. Lessons: Although being a rare condition, a coronary artery CTA examination can be utilized to screen for congenital absence of RCA and other varieties of cardiovascular malformation whereas SCA can be performed to confirm the diagnosis.